Active vitamin D is cardioprotective in experimental uraemia but not in children with CKD Stages 3–5. Issue 3 (30th November 2020) - Schön, Anne; Leifheit-Nestler, Maren; Deppe, Jennifer; Fischer, Dagmar-Christiane; Bayazit, Aysun K; Obrycki, Lukasz; Canpolat, Nur; Bulut, Ipek Kaplan; Azukaitis, Karolis; Yilmaz, Alev; Mir, Sevgi; Yalcinkaya, Fatos; et al.
Abstract: Background: Uraemic cardiac remodelling is associated with vitamin D and Klotho deficiency, elevated fibroblast growth factor 23 (FGF23) and activation of the renin–angiotensin system (RAS). The cardioprotective properties of active vitamin D analogues in this setting are unclear. Methods: In rats with 5/6 nephrectomy (5/6Nx) treated with calcitriol, the cardiac phenotype and local RAS activation were investigated compared with controls. A nested case–control study was performed within the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study, including children with chronic kidney disease (CKD) Stages 3–5 [estimated glomerular filtration rate (eGFR) 25 mL/min/1.73 m 2 ] treated with and without active vitamin D. Echocardiograms, plasma FGF23 and soluble Klotho (sKlotho) were assessed at baseline and after 9 months. Results: In rats with 5/6Nx, left ventricular (LV) hypertrophy, LV fibrosis and upregulated cardiac RAS were dose-dependently attenuated by calcitriol. Calcitriol further stimulated FGF23 synthesis in bone but not in the heart, and normalized suppressed renal Klotho expression. In the 4C study cohort, treatment over a mean period of 9 months with active vitamin D was associated with increased FGF23 and phosphate and decreased sKlotho and eGFR compared with vitamin D naïve controls, whereas LV mass index did not differ between groups. Conclusions: Active vitamin D ameliorates cardiac remodelling and normalizes renal Klotho expression in 5/6Nx rats but does not improve the cardiac phenotype in children with CKD Stages 3–5. This discrepancy may be due to further enhancement of circulating FGF23 and faster progression of CKD associated with reduced sKlotho and higher serum phosphate in vitamin D-treated patients.